Developing Digital Web-Based Teaching Materials for Indonesian Subject - Chece Nurmalasari; Nurhikmah H; Hamsu Abdul Gani (Universitas Sebelas Maret, 2022)
This research was conducted to propose digital web-based teaching materials using link trees. Research is a research and development study that aims to examine the level of need, practicality and effectiveness of developing digital web-based materials in Indonesian Subjects for seventh grade students of Amir Islam Panyula Junior High School (SMP), Bone Regency. The type of research used is the type of development research (R and D). The development model used is the ADDIE model. Data collection techniques use observation techniques, questionnaires, documentation, pretest and posttest. Data analysis uses data analysis of validity, practicality and effectiveness by using data analysis techniques n_gain to find out how the level of effectiveness of digital web-based teaching materials is developed. Based on this research, it can be concluded that the teaching materials developed meet valid criteria with a validity level of 4.7, practical with a practicality level of 4.5 tested practically and effectively with an effectiveness level of 50 so that the teaching materials are effective enough to be used in the field. Digital web teaching materials are recommended for use in real learning.